Discharge current distribution in stratified soil under impulse discharge - Fajingbesi, Fawwaz Eniola; Midi, Nur Shahida; Elsheikh, Elsheikh Mohamed Ahmed; Yusoff, Siti Hajar (IOP Publishing, 2017)
The mobility of charge particles traversing a material defines its electrical properties. Soil (earth) have long been the universal grounding before and after the inception of active ground systems for electrical appliance purpose due to it semi-conductive properties. The soil can thus be modelled as a single material exhibiting semi-complex inductive-reactive impedance. Under impulse discharge such as lightning strikes to soil this property of soil could result in electric potential level fluctuation ranging from ground potential rise/fall to electromagnetic pulse coupling that could ultimately fail connected electrical appliance. In this work we have experimentally model the soil and lightning discharge using point to plane electrode setup to observe the current distribution characteristics at different soil conductivity [mS/m] range. The result presented from this research indicate above 5% shift in conductivity before and after discharge which is significant for consideration when dealing with grounding designs. The current distribution in soil have also be successfully observed and analysed from experimental result using mean current magnitude in relation to electrode distance and location, current density variation with depth all showing strong correlation with theoretical assumptions of a semi-complex impedance material.